Current outlook on the development of Malaysian Chinese private higher education in design - Chen, Tien Li; Siek, Hwee Ling * (National Chengn Kung University, Taiwan, 2018)
This paper describes the impact of national, economic, and educational policies on the development design education in Malaysia’s private educational institutions. Through historical and content analysis and interviews with experts, this article offers a complete timeline of the development of Malaysia’s Education in Design among private educational institutions founded by Malaysian Chinese, the history of Malaysia’s private education in design and the evolution of Malaysia’s national educational policies. We divide this history into the four periods of Chaotic (before 1965), Seeding (1966-1995), Germination (1996-2005), and Standardization (2006 onward). Our historical review concludes that education providers focus largely on providing basic training for students with the sole purpose of securing a job immediately after their graduation.